Role of Fine Needle Aspiration Cytology (FNAC) In Evaluation of Thyroid Nodules: Fine-Needle Aspiration Cytology for Thyroid Neoplasm - Khan, Muhammad Moiz Ullah; Khan, Muhammad Wasi Ullah; Ali, Syed Faizan; Shakil, Saad; Aftab, Ali Akber; Abbas, Tahir Ghulam (Pakistan Journal of Health Sciences, 2024)
Fine-Needle Aspiration Cytology (FNAC) is a practical and low-cost preoperative method for evaluating thyroid gland neoplasms that provides a correct diagnosis fast and with minimal hazards. Thyroid nodules are communal, being existing in up to 50% of the aged populace. The mainstream are benign with thyroid cancer representing an uncommon clinical problem. Objective: To assess the role of FNAC of thyroid gland cancers in our environment and the diagnostic performance of the FNAC in identifying these conditions. Methods: A retrospective analysis was conducted on 120 individuals who had thyroid swelling when they were first seen and who had surgery between January 2020 and December 2022. Patients with findings from postoperative surgical histopathology and preoperative fine needle aspiration cytology were included in the research. The FNAC's diagnostic accuracy, positive and negative predictive values, sensitivity, and specificity were all calculated. Results: Out of 120 patients, 18 (15%) were male and 102 (85%) were female. Out of 120 cases, by histopathological examination FNAC showed 79 cases as benign and 41 cases as malignant lesions. Conclusions: According to this research, FNAC is a reasonably accurate approach for identifying thyroid gland cancers, with good sensitivity and specificity. Thus, it can be a useful resource for preoperative counselling on the characteristics of the neoplasms and their outcomes as well.